The Art and Sustainable Aspects of Natural Dyeing in KANAWIDA Hand Drawn Batik (Green Batik) - July Hidayat; Fatmahwaty Fatmahwaty (IPTEK Journal of Proceedings Series, 2014)
Indonesian batik has been recognized by UNESCO as the intangible cultural heritage of Indonesia. The ironic thing happened when Indonesian batik export is rejected by the market of European Union because of wearing artificial dyes and thus is categorized as eco unfriendly product. The chemical waste of artificial dyeing process can cause damage to environment and skin health of batik users. Therefore, the research and publication of natural dyeing materials and techniques in batik is needed to disseminate the techniques to craftmen and promote the use of green batik as a life style. In this paper, we discuss the art and sustainable aspects of natural dyeing in the making process of Kanawida Batik, one famous home industry of green batik in Banten and DKI Jakarta provinces. Using case study research method, we examine the art characteristics and implementation of sustainability requirements in the natural dyeing. The several results are: (1) knowledge about natural color sources and methods to produce it from natural materials, especially that are came from the richness and variety of Indonesian plants, (2) the manual and art characteristics of natural dyeing, (3) knowledge about how to implement sustainability in home industry of batik.